IMPACT OF IMPLEMENTING THE COMPETENCY-BASED MERDEKA CURRICULUM IN SECONDARY EDUCATION ON ENHANCING 21ST CENTURY SKILLS AND MEETING THE DEMANDS OF THE COMPETITIVE JOB MARKET - Kasmudin Mustapa; Indah Suciati, Nursupiamin, Wahyuni H. Mailili, Hajerina (International Journal of Teaching and Learning, 2023)
This study explores the impact of implementing the Competency-Based Merdeka Curriculum in secondary education on enhancing 21st-century skills and meeting the competitive job market demands. The curriculum's innovative approach, emphasizing practical competencies alongside academic knowledge, is examined for its effectiveness in aligning with contemporary skill requirements and preparing students for the dynamic job market. Through a comprehensive analysis of key findings, the study unveils the curriculum's significant influence on student achievement, employability, and developing critical skills such as critical thinking, creativity, communication, collaboration, and adaptability. Despite initial implementation challenges, the curriculum showcases resilience and adaptability, evidenced by successful integration in educational settings. The implications for educational policy and practice are discussed, providing valuable insights for educators and policymakers seeking to enhance the curriculum's effectiveness. Looking forward, the study emphasizes the role of competency-based education in shaping a responsive and relevant education system. Ongoing research and incorporating international best practices are recommended to continually refine and  optimize  the  Competency-Based  Merdeka  Curriculum,  ensuring  its adaptability and success in addressing the evolving demands of the 21st-century job market.